Toward a pedagogy for faculty and student co-responsibility in curating college museum exhibitions. (April 2015) - Rodgers, Susan
When undergraduates work with college faculty on complex research projects, the students are often asked to take on the role of "secondary-level" gatherers of data. This can be legitimate: the students have no graduate training and the faculty mentor is more experienced in research design and analysis. This study, however, offers an alternative model for student/faculty joint research: a model for pedagogy on the arts in anthropology that fosters stronger degrees of student agency and "ownership" of a museum project. At issue was a college art gallery exhibition called "Transnational Ikat: An Asian Textile on the Move" co-curated by an anthropologist (the author) and undergraduates. Some institutions invite undergraduates to curate exhibitions via museum studies seminars. However, the model discussed here had more scope: the team did ethnographic fieldwork in Bali, then cowrote the exhibition website, and then led gallery tours. Co-ownership of the entire undertaking was fostered in all stages.